2011
DOI: 10.1007/s00726-011-0837-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulation of IGF-I by alterations in post-exercise macronutrients

Abstract: This investigation sought to examine the contributions of exercise and nutrient replenishment on in vivo regulation of the insulin-like growth factor-I (IGF-I) axis components. Eight college-aged males completed three high-intensity interval training (HIIT) protocols followed by three post-exercise nutritional protocols: (1) placebo (EX); (2) carbohydrate only (CHO); and (3) essential amino acid/carbohydrate (EAA/CHO). Samples were analyzed for growth hormone (GH), free IGF-I, IGFBP-1, IGFBP-2, insulin, hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…Foster et al [29] reported that acute aerobic exercise increases IGFBP-1 concentration in young men, and that this is partially reduced by post-exercise carbohydrate consumption with a corresponding increase in circulating insulin level; however, the effect of exercise on diet-induced changes in IGFBP-1 was not studied as in the present report. Ngo et al [28] reported that 11 days of daily aerobic exercise with a low fat (<10%) and high carbohydrate 70–75%) diet increased serum IGFBP-1 concentrations by 53%.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Foster et al [29] reported that acute aerobic exercise increases IGFBP-1 concentration in young men, and that this is partially reduced by post-exercise carbohydrate consumption with a corresponding increase in circulating insulin level; however, the effect of exercise on diet-induced changes in IGFBP-1 was not studied as in the present report. Ngo et al [28] reported that 11 days of daily aerobic exercise with a low fat (<10%) and high carbohydrate 70–75%) diet increased serum IGFBP-1 concentrations by 53%.…”
Section: Discussioncontrasting
confidence: 55%
“…Two previous studies reported the effect of combined diet and exercise on IGFBP-1 concentrations [28,29]. Foster et al [29] reported that acute aerobic exercise increases IGFBP-1 concentration in young men, and that this is partially reduced by post-exercise carbohydrate consumption with a corresponding increase in circulating insulin level; however, the effect of exercise on diet-induced changes in IGFBP-1 was not studied as in the present report.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast to measuring total serum IGF-1 levels, we utilized a commercial IGF-1 ELISA kit from R&D Inc. (Minneapolis, MN, USA) to determine the free serum IGF-1 concentrations, which represent the “bioavailable” portion of the circulating IGF-1 pool [16]. Serum concentrations of IGFBP-1, IGFBP-3, insulin, and corticosterone were also determined by ELISA kits (R&D Systems, Minneapolis, MN, USA) in accordance with the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Takenaka et al [15] reported that dietary restriction of signal essential amino acid (EAA) decreased IGF-1 production, suggesting that adequate EAA in diet might be required for the IGF-1 synthesis. A recent study regarding acute regulation of the IGF-1 system by macronutrients further demonstrated that EAA/carbohydrate mixture ingestion following high-intensity exercise promoted a significant increase in circulating free IGF-1 levels [16].…”
Section: Introductionmentioning
confidence: 99%
“…Once AKT is activated it can also cause the phosphorylation of mTOR [26]. Furthermore, resistance training and leucine supplementation can possibly increase the release of insulin-like growth factor 1 (IGF1) in the body [12, 24]. …”
Section: Introductionmentioning
confidence: 99%